If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5x+24=5(x-1/2)
We move all terms to the left:
5x+24-(5(x-1/2))=0
We add all the numbers together, and all the variables
5x-(5(+x-1/2))+24=0
We multiply all the terms by the denominator
5x*2))-(5(+x-1+24*2))=0
We add all the numbers together, and all the variables
5x*2))-(5(x+47))=0
We add all the numbers together, and all the variables
5x*2))-(5(x=0
Wy multiply elements
10x^2=0
a = 10; b = 0; c = 0;
Δ = b2-4ac
Δ = 02-4·10·0
Δ = 0
Delta is equal to zero, so there is only one solution to the equation
Stosujemy wzór:x=\frac{-b}{2a}=\frac{0}{20}=0
| 4x^2+56x/3-80=0 | | 84+76+77+75+2x/6=80 | | 25/6=-x+1/2-8/3x | | 4x^2+56/3*x-80=0 | | x+2/3=13/9;{5/9,2/3,7/9} | | +2y-8=3(y-11) | | 200=1.5x | | X+2x+1+2x+3=29 | | (m-2)=-2(-2m+6) | | (3+4x)=16 | | x/2+x=3 | | (m-2)=-2(-2m+6 | | 3(x5)=2(x+5) | | X2+4x=20 | | 3(x5)=2(x+50 | | 14+1/3x=180 | | 7/4w-1=20 | | 9x-(2x+8)=20 | | 0,05x+0.10(200-x)=0.45x | | -3/2=-3/7w-2/3 | | 30x+5x^2=3600 | | 2x(x+3)-(x^2-9)=0 | | x+2x+3x=5.5 | | √2x+10=√x+3 | | 7x-2x9=5x-6 | | 3x(x+3)-(x^2-9)=0 | | y^-1/2=7 | | 5x+24=5(x-1/2) | | x^2=-(64/9)+8x | | 2*x-10=x+3 | | +12-3D=5d+6 | | x^2=(64/9)-8x |